Design and Analysis of a Vertical Axis Ocean Current Turbine Tunnel Using SolidWorks Computational Fluid Dynamics - Hardi Gunawan; Nanang Ruhyat; Sentot Novianto (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2024)
The development of renewable energy in the marine power generation sector presents a promising approach to producing electrical energy in a sustainable and environmentally friendly manner. Indonesia, with its vast oceanic territory, holds significant potential for harnessing marine energy. However, the relatively slow speed of ocean currents in the region, typically ranging from 0.1 m/s to 1.5 m/s, poses a challenge to the efficiency of marine power generation. To overcome this limitation, this research focuses on the design and analysis of a vertical-axis ocean current turbine tunnel aimed at increasing the speed of ocean currents, thereby enhancing the overall efficiency of energy production. The study combines a thorough literature review with experimental research methods, utilizing SolidWorks Computational Fluid Dynamics (CFD) software to simulate the tunnel's impact on ocean current velocity. The simulations reveal that the tunnel construction significantly boosts current speeds, increasing them from 1.0 m/s to 1.7 m/s, and from 1.5 m/s to 2.6 m/s. This increase in velocity directly translates to higher kinetic energy available for conversion into electrical power by the turbine. Moreover, the study shows that the tunnel construction contributes to a more uniform flow of ocean currents, as evidenced by the Reynolds numbers obtained—100.250 at a current speed of 1.0 m/s and 150.375 at 1.5 m/s. These values, being below 2000, indicate laminar flow conditions within the tunnel, which are beneficial for optimizing turbine performance by reducing turbulence and ensuring a stable energy output. The findings underscore the effectiveness of the tunnel design in improving the efficiency of vertical-axis ocean current turbines, making it a viable solution for enhancing renewable energy production in regions with low ocean current speeds.